1985
DOI: 10.3109/00016348509156729
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Trial of Metoprolol‐hydralazine Treatment in Hypertension During Pregnancy

Abstract: In an open, controlled trial, treatment with a combination of metoprolol and hydralazine was compared with non-pharmacological management of mild and moderate hypertension in pregnancy. One hundred and sixty-one women participated in the study. The drug-treated group showed significantly better blood pressure control than the group not given antihypertensives. Induction of labor before term, because of maternal or fetal complications, was somewhat more frequent in the control group. Nine women in the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…To estimate the effect of antihypertensive agents in pregnant women with mild to moderate hypertension, we found 18 studies which reported data on stillbirths [10,14,58-73] and twenty studies which reported data on perinatal mortality [14,58,60,61,63-66,68,69,71-80] (Table 3). The effect of antihypertensive drugs showed no effect for stillbirths (RR= 1.14; 95% CI: 0.60 to 2.17) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…To estimate the effect of antihypertensive agents in pregnant women with mild to moderate hypertension, we found 18 studies which reported data on stillbirths [10,14,58-73] and twenty studies which reported data on perinatal mortality [14,58,60,61,63-66,68,69,71-80] (Table 3). The effect of antihypertensive drugs showed no effect for stillbirths (RR= 1.14; 95% CI: 0.60 to 2.17) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Prospective controlled studies of metoprololhydralazine, nifedipine and labetalol-methyldopa treatment administered to pregnant women with mild PIH, unclassifiable hypertension or mild PE showed no significant improvement of pregnancy outcome as compared to the non-treated group. [95][96][97][98] Labetalol had no effect on development of proteinuria in a trial of 114 women with PIH and nifedipine had no effect on PE-related hypocalciuria as compared to the control than those of the non-treated/placebo group. Decrease in mean arterial pressure of 10 mmHg was associated with a 145 g decrease in mean birth weight, as found in a post-hoc analysis.…”
Section: Mild To Moderate Hypertensionmentioning
confidence: 99%
“…Many feel justified to start treatment if there is a rise in BP in the second trimester (4,11). From the mothers' point of view, Hogstedt et al (23) did not find it mandatory with pharmacological treatment in mild to moderate hypertension but they did not differentiate between chronic hypertensive, gestational hypertensive and preeclamptic women. In our study, the pregnancy length was significantly shorter in the group with untreated mild hypertension compared to normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%